PEMBELAJARAN NILAI PEDULI SESAMA BERBASIS FILM ANIMASI KISAH NABI PADA ANAK USIA DINI: STUDI KASUS DI RA AL-IZZAH - Nurhana Aulia; Atin Fatimah; Fadlullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has transformed the way young children learn, including the use of animated films as a medium for character value education. RA Al-Izzah utilizes the KABI animated series depicting stories of the prophets as a learning medium to cultivate the value of caring for others among children. This study aims to analyze and describe the use of prophet-story animated films as a learning medium, their impact on the development of caring values, and the supporting and inhibiting factors in their implementation at RA Al-Izzah. This study employed a qualitative case study approach. The research subjects were children of group B7 Lotus, with the classroom teacher serving as an informant. Data were collected through non-participant observation, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. Data validity was tested through source and technique triangulation. The results show that the prophet-story animated films were used routinely every Thursday through screening, teacher guidance, and post-viewing recalling activities. The use of this medium positively affected the emergence of caring behavior in children, reflected in sharing, helping, empathy, and cooperation. Supporting factors included the attractiveness of the medium, the teacher's active role, and adequate facilities, while the main inhibiting factor was children's limited attention span. This study concludes that prophet-story animated films are effective as a medium for instilling the value of caring for others in early childhood when accompanied by consistent teacher guidance and value reinforcement. Keywords: animated film, prophet stories, caring for others, early childhood, case study